Performance Analysis of Financial Ratios of PT Telkom Indonesia Tbk - Aisyah Afifah Anastasya S; Devi Krisdayanti Laia; Elfi Juliana Cibro; Nadia Theresia Sirait; Sabda Dian Nurani Siahaan (Asian Journal of Applied Business and Management, 2023)
This study aims to find out the financial description of PT Telkom Indonesia Tbk and help investors and other parties understand the financial condition and operations of the company from 2019 to 2022. This research was conducted at PT Telkom Indonesia Tbk which can be accessed via the official website at https://www.telkom.co.id/sites. Data analysis used a descriptive statistical analysis method. The results showed that PT Telkom Indonesia made significant progress in improving its financial performance. Financial ratios show that the company's financial performance is better than the previous period. The company has succeeded in increasing its liquidity, activity, solvency, and profitability ratios. The company has struck a balance between developing good cash flow and increasing its total assets.